'Observation' as China's civic education pedagogy and governance: an historical perspective and a dialogue with Michel Foucault. Issue 6 (2nd November 2019) - Zhao, Weili
ABSTRACT: This paper examines China's civic education discourses from a historical and cross-cultural perspective. It unpacks observation as a political–cultural–spatial pedagogy, underpinning Confucius' educational envisioning, Mao's domination in the Cultural Revolution Movement, and Xi's China/ese Dream propaganda. Drawing upon Foucault's provocation of the Western gaze, this paper historicizes Confucius, Mao, and Xi's discourses to explicate a Chinese observation diagram. With Confucius, observation works as an onto-hermeneutic principle, grounding China's cosmology and sovereign-subject governance. With Mao, observation becomes a panoramic domination-surveillance mechanism, which, coupled with a Confucian punitive shame, empowers the proletarian mass in excluding-purging the bourgeois as class enemies. With Xi, observation turns into a symbolic governing technology of self, subjecting its citizenry to re-branded Confucian values toward realizing a participatory China/ese Dream. In so doing, this paper shows the parallels and contradistinctions between the Chinese observation and the Western gaze in historically and structurally ordering knowledge production and social-educational governance.